Peluruhan Batang Grafit Baterai Bekas Dengan Metode Electrochemical Exfoliation Menggunakan Pelarut Amonium Sulfat Dan Kalium Sulfat - Michael Hutapea; Amun Amri; Rozanna Sri Irianty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
One way to exfoliate the graphene is by electrochemical exfoliation graphite (EEG) method which is the method for graphene synthesis by splitting graphite material into graphene sheets through the electrochemical process. The objective of this research is to synthesis graphene from used battery graphite rod using [(NH4)2SO4] and (K2SO4) and to determinethe effect of solvent variation and solvent concentration on the graphite decay rate. The results showed that the increase of solvent concentration increased the yield. The highestyield for the solvents [(NH4)2SO4] and (K2SO4) were 10,6% and 15,3% repectively. The result of UV-Vis spectrophotometric wave peak was ~270 nm that indicating the peak of graphene.Raman spectroscopy analysis result showed that the graphene was nanoplatelet (multi-layer) and the number of graphene layers was ~3-10 layer. FTIR analysis showed the functionalgroups after decay process on graphite. The best conductivity was K2SO4 solvent 1,5 M is 0,0621 Ω-1.cm-1.Keywords: electrochemical exfoliation graphite, graphene, graphite.